A IMPORTÂNCIA DA GESTÃO NUTRICIONAL NO CONTEXTO DA GESTÃO DO ESPORTE: UMA REVISÃO SISTEMÁTICA - Ligia Prestes Fernandes; Bruna Marcacini Azevedo (Universidade Salgado de Oliveira, 2019)
Still recent, studies on sports management began in Brazil in the 1980s, starting with a demand that had its first steps in the United States of the 1960s. From this point, there was an increase in the collection for the development of professionalism among those responsible for investments in the sports world, with the development of management complexity. Within this administrative system, there is an aspect that has been little studied and put into practice: the nutritional management of high-performance athletes and their importance for the performance and recovery of these individuals. The correct nutritional management, here understood as the planned administration of adequate nutrition to the athlete, has a direct impact on the management of a sports team. Either in the adequate prevention of injuries, with the reduction of them; either for a faster recovery of injured athletes, shortening their time to return to sports activities and/or decrease their professional inactivity. These points have a direct impact on the financial and sporting aspects of an institution that manages high-performance sports, and should, therefore, be the object of attention and concern of managers who administer teams and entities that manage the sport. Based on this, a literature review was carried out, and articles were reviewed that demonstrate the importance of nutritional management for sports club and sports management, considering that the correct nutrition management of elite athletes has, among other aspects, also impacts on the financial aspects and sports institutions of an institution that manages high-performance sports.